Sertoli Cell Function in Young Males with Metabolic Syndrome - Saikia, Uma Kaimal (Indian J Endocrinol Metab, 2019)
CONTEXT: The last few decades have witnessed an alarming increase in the prevalence of the metabolic syndrome (MetS) worldwide including India. Apart from the known risks of MetS in terms of cardiovascular risk and mortality, there is increasing evidence that it also leads to alteration in testicular function and fertility. AIMS: To assess the presence of hypogonadism and Sertoli cell dysfunction in young adult males with MetS and correlate these parameters with different components of the MetS. SETTINGS AND DESIGN: Cross-sectional study conducted in the Department of Endocrinology, Gauhati Medical College, a tertiary care hospital in North East India. SUBJECTS AND METHODS: Young adult males with MetS aged 20–40 years and age-matched healthy males who served as controls were examined clinically. Laboratory investigations done in the fasting state included blood glucose, lipid profile, serum follicle-stimulating hormone (FSH), inhibin B and total testosterone (Te). Semen was collected after 3 days abstinence and analysis done. STATISTICAL ANALYSIS: Baseline parameters were presented as median and ‘Kruskal–Wallis’ test was used to compare them. Pearson test and multiple regression analysis were used to assess the correlation and association between variables. RESULTS: Fifty cases with MetS and 30 controls were included in the study. Subjects with MetS had significantly lower levels of total Te, FSH and inhibin B. They also had significantly lower semen volume, sperm count and total as well as progressive motility. There was a significant negative correlation of waist circumference and positive correlation of inhibin B with total sperm count. A significant negative association of serum triglycerides with semen volume was also found. CONCLUSION: MetS is a state of hypogonadotropic hypogonadism as reflected by low total Te, FSH and inhibin B levels with semen abnormalities reflecting Sertoli cell dysfunction.